EFEKTIVITAS PENYEMBUHAN LUKA BAKAR AKIBAT PEMBERIAN GEL ESTRAK ETANOL DAUN CENGKEH (Syzygium aromaticum L.) PADA KELINCI (Oryctolagus cuniculus) - Puruhita, Ranatri; Aldila, Silvy; Ariyani, Destiana Putri (Jurnal Farmasi & Sains Indonesia, 2025)
Burns are damage to the organs that can happen when heat exposure from fire, chemicals, electricity, or radiation damages or destroys skin tissue. For burns, topical treatment can hasten the healing process. Because clove leaves have antiseptic qualities and antibacterial and anti-inflammatory activity, their secondary metabolites—flavonoids, tannins, and saponins—can be used to treat open wounds and stop infection. The purpose of this study is to create a gel formulation using clove leaf extract that will treat burn wounds without causing skin infections. Two formulations of the gel preparation, each with a 10% and 15% concentration, were evaluated on test rabbits. Using a hot iron plate, the rabbits' backs were shaved to cause burns. Clove leaf extract gel was used for the treatment group, Bioplacenton® was used as the positive control, and gel base was used as the negative control. Measurements of the wound's diameter were taken on days 0 and 15, and SPSS was used to analyze the results. Clove leaf extract burn gel is 60.98% effective in formula 1 and 77.16% effective in formula 2. Formula 2 is the gel formulation that works best for treating rabbit burns.